2018
DOI: 10.1177/0022427818757283
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Housing Demolitions on Crime in Buffalo, New York

Abstract: Objectives: From 2010 through 2015, the city of Buffalo demolished over 2,000 residences. This study examines whether those demolitions resulted in crime reductions. Methods: Analysis was conducted at microplaces matching demolished parcels to comparable control parcels with similar levels of crime. In addition, spatial panel regression models were estimated at the census tract and quarterly level, taking into account demographic characteristics of neighborhoods. Results: We find that at the microplace lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 55 publications
(75 reference statements)
0
16
1
Order By: Relevance
“…Boessen and Chamberlain (2017) also find that the presence of abandoned housing is positively correlated with property, but not violent crime. As a departure from these studies, Branas and colleagues (2012) find that increases in vacant housing are associated with increases in aggravated assault and Wheeler et al (2018) find evidence that demolishing abandoned houses in Buffalo, New York, was associated with reductions for both violent and nonviolent calls at the microgeographic level. However, effects did not consistently hold for census tracts.…”
Section: Vacant Housing and Crimementioning
confidence: 99%
See 1 more Smart Citation
“…Boessen and Chamberlain (2017) also find that the presence of abandoned housing is positively correlated with property, but not violent crime. As a departure from these studies, Branas and colleagues (2012) find that increases in vacant housing are associated with increases in aggravated assault and Wheeler et al (2018) find evidence that demolishing abandoned houses in Buffalo, New York, was associated with reductions for both violent and nonviolent calls at the microgeographic level. However, effects did not consistently hold for census tracts.…”
Section: Vacant Housing and Crimementioning
confidence: 99%
“…In particular, aspects of the built environment may be important to consider, given that the appearance or presence of certain structures may shape criminal opportunity and perceptions of neighborhood investment (Weisburd et al 2012). One aspect of the built environment suggested by prior research is the presence of abandoned housing, which has been associated with crime at the neighborhood level (Boessen and Chamberlain 2017;Branas, Rubin, and Guo 2012;Hannon and Cuddy 2006;Cohen et al 2003) and microgeographic level (Wheeler, Kim, and Phillips 2018). However, this body of work remains limited in important respects.…”
mentioning
confidence: 99%
“…Branas et al (2018) observed a 13% reduction in crime overall and a near 30% reduction in gun violence following vacant lot remediation. Wheeler et al (2018) also found reductions in crime following the demolition of vacant buildings but found statistically significant results for only a small radius. It seems that vacancy remediation is a potential target for crime reduction, but that a further understanding of the effect of vacancy on crime is necessary.…”
Section: Literature Reviewmentioning
confidence: 92%
“…18 The grid size corresponds with the finding from a similar city that demolition effects were strongest within a 152 m buffer of each demolition. 11 To adjust our models for time-varying demographic patterns, we obtained 2000 decennial census data and estimates from the 5-year American Community Survey ending each year from 2009 to 2019, for population, poverty rate and housing occupancy rate by census tract. For those years, we used inverse distance weighting to assign values from census tract centroids to grid squares.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Recent studies have found that demolitions can also reduce violence, including firearm violence. In Buffalo, New York, Wheeler and colleagues 11 found that demolitions were associated with violence reductions up to several blocks away, and indications that cumulative demolitions reduced firearm violence at the census tract level. 11 In Detroit, Michigan, Jay and colleagues 3 found that cumulative demolitions within census block groups were associated with reduced firearm assaults.…”
Section: Introductionmentioning
confidence: 99%